Analysis of speech fluency in Williams syndrome - Rossi, Natalia Freitas [UNESP]; Sampaio, Adriana; Goncalves, Oscar F.; Giacheti, Célia Maria [UNESP] (Pergamon-Elsevier B.V. Ltd, 2011)
Williams syndrome (WS) is a neurodevelopmental genetic disorder, often referred as being characterized by dissociation between verbal and non-verbal abilities, although the number of studies disputing this proposal is emerging. Indeed, although they have been traditionally reported as displaying increased speech fluency, this topic has not been fully addressed in research. In previous studies carried out with a small group of individuals with WS, we reported speech breakdowns during conversational and autobiographical narratives suggestive of language difficulties. In the current study, we characterized the speech fluency profile using an ecologically based measure - a narrative task (story generation) was collected from a group of individuals with WS (n = 30) and typically developing group (n = 39) matched in mental age. Oral narratives were elicited using a picture stimulus - the cookie theft picture from Boston Diagnosis Aphasia Test. All narratives were analyzed according to typology and frequency of fluency breakdowns (non-stuttered and stuttered disfluencies). Oral narratives in WS group differed from typically developing group, mainly due to a significant increase in the frequency of disfluencies, particularly in terms of hesitations, repetitions and pauses. This is the first evidence of disfluencies in WS using an ecologically based task (oral narrative task), suggesting that these speech disfluencies may represent a significant marker of language problems in WS. (C) 2011 Elsevier Ltd. All rights reserved.
Keywords: Fluency; Oral narrative; Language; Williams syndrome